Disconnecting from Social Networks - Briana, Maria; Koloniari, Maria; Koulouris, Alexandros; Vraimaki, Eftichia (Qualitative and Quantitative Methods in Libraries, 2021)
Today, more than half of the world’s population uses social media, and the ongoing Coronavirus pandemic is a major contributing factor to their expedited growth. However, negative experiences associated with social networking, such as fatigue and overload, can lead to SNS abandonment. Given the widespread utilization of social media by libraries of all types, user discontinuance decisions are crucial to the formulation of libraries’ digital marketing strategy. In this context, this study investigates public library patrons’ intention to discontinue using Facebook, permanently or intermittently, and/or replace it with another network. Preferences regarding the content posted by libraries are also examined, as it has been found to affect social media fatigue and abandonment.